2023
DOI: 10.1038/s41467-023-36401-7
|View full text |Cite
|
Sign up to set email alerts
|

Surface engineering of inorganic solid-state electrolytes via interlayers strategy for developing long-cycling quasi-all-solid-state lithium batteries

Abstract: Lithium metal batteries (LMBs) with inorganic solid-state electrolytes are considered promising secondary battery systems because of their higher energy content than their Li-ion counterpart. However, the LMB performance remains unsatisfactory for commercialization, primarily owing to the inability of the inorganic solid-state electrolytes to hinder lithium dendrite propagation. Here, using an Ag-coated Li6.4La3Zr1.7Ta0.3O12 (LLZTO) inorganic solid electrolyte in combination with a silver-carbon interlayer, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 59 publications
0
50
0
Order By: Relevance
“…This non-ideal voltage behavior (plateaus and sloping regions not observed in liquid electrolyte cells with the same cathode) followed by capacity loss at high C discharge rates suggests that some degree of void formation is still present in our 300 nm of gold interlayer cells, especially at high discharge rates. 16,17 Due to the lower capacity accessed beyond the C/8 discharge rate (presumably due to void formation), we maintained a constant discharge rate of C/8 and applied a variable charge rate (C/12, C/8, C/3, C/2, 1C) to freshly made cells of the same construction. Figure 1b shows the voltage profiles for a 300 nm gold interlayer cell discharged at C/12 and C/8 with 0.3 MPa external stack pressure at roomtemperature conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This non-ideal voltage behavior (plateaus and sloping regions not observed in liquid electrolyte cells with the same cathode) followed by capacity loss at high C discharge rates suggests that some degree of void formation is still present in our 300 nm of gold interlayer cells, especially at high discharge rates. 16,17 Due to the lower capacity accessed beyond the C/8 discharge rate (presumably due to void formation), we maintained a constant discharge rate of C/8 and applied a variable charge rate (C/12, C/8, C/3, C/2, 1C) to freshly made cells of the same construction. Figure 1b shows the voltage profiles for a 300 nm gold interlayer cell discharged at C/12 and C/8 with 0.3 MPa external stack pressure at roomtemperature conditions.…”
mentioning
confidence: 99%
“…Promises of higher energy density, faster charging speed, and improved safety have created much excitement for the emergence of solid-electrolyte-containing batteries in both industry and academia. Among several different classes of solid electrolytes is a garnet-type ceramic electrolyte, Li 7 La 3 Zr 2 O 12 (LLZO), which has received attention due to its relatively high ionic conductivity and impressive chemical stability with metallic lithium. Nonetheless, commercialization of this technology is hindered due to interfacial instabilities which can lead to void formation followed by dendritic growth of lithium, eventually shorting the battery. , Specifically, several studies have reported that the pristine lithium/LLZO interface generates voids on discharge between Li metal and the solid electrolyte due to differential kinetic rates between lattice Li self-diffusion, Li plastic flow, and dynamic lithium stripping. As a result of this interfacial instability, current focusing or localized electroplating of lithium is common, which can lead to internal short-circuiting of the cell in the following charge step. Recently, it was revealed that controlling the interface between the solid electrolyte (LLZO) and Li metal with an “interlayer” plays a critical role enabling commercially relevant critical current density (CCD) at room-temperature conditions. , A wide array of materials such as metals, alloys, carbonaceous compounds, oxides, halides, and nitrides were investigated as potential interlayer materials which are proposed to improve interfacial contact between Li metal and LLZO and facilitate a uniform Li-ion flux. To date, the best-performing LLZO solid-state batteries in the peer-reviewed literature were fabricated by the battery team at Samsung Advanced Institute of Technology (SAIT) using an amorphous carbon system, where the utilization of mixed nano-sized carbon in a porous nanocomposite ∼3 μm thick enabled commercially relevant current densities (∼2.5 mA/cm 2 ) with hundreds of stable electrochemical cycles at room temperature with no external stack pressure (>250 cycles, 99.6% capacity retention) …”
mentioning
confidence: 99%
“…An anodeless cell design wherein Li metal anodes are generated in situ during charging, such as ASSBs employing Ag-C anodes, offers significant advantages. [37,139,237] Finally, we have observed a growing number of studies on the low-pressure operation of ASSBs. Additionally, numerous previously conducted investigations on next-generation electrode applications for ASSBs (e.g., Si, Sn, Sb), which are based on testing using SE powder-based uniaxial pressurized cells, need to be re-examined for practical assessment.…”
Section: Discussionmentioning
confidence: 99%
“…An anodeless cell design wherein Li metal anodes are generated in situ during charging, such as ASSBs employing Ag–C anodes, offers significant advantages. [ 37,139,237 ]…”
Section: Discussionmentioning
confidence: 99%
“…The proper interlayer material must be used to create high-performance SSBs. The flexibility and softness of polymer-based SSEs make them a popular choice for interfacial buffer layers. , Soft polymer electrolytes, such as LEs, may conformally cover SSEs and electrodes and are scalable. The major purpose of the interlayer is to deflect lithium plating away from the solid electrolyte, thereby reducing the likelihood of dendritic penetration and preventing Li metal from coming into contact with the solid electrolyte.…”
Section: Solutions To Address Interface Issuesmentioning
confidence: 99%